Branding of electricity in B2B markets - Rolanda Simenaite 1986- (2013)
Branding has gained an important role in the B2B (business-to-business) market. Liberation of the energy markets in recent years has increased competition and branding could create a competitive advantage. This thesis analyzes the branding of electricity in a business-to-business context. In depth, this thesis explores the supplier of electricity brand importance for business customers in both Icelandic and Lithuanian B2B markets. The focus of the thesis is to research how much brands matter for businesses when choosing their electricity supplier. Additionally, the thesis examines the main B2B brand benefits and what factors contribute towards the loyalty business customers have to the brand. The theoretical chapter describes and explores the B2B branding concept, its importance, processes and links to the organizational buyers. Moreover, the theory gives an overview about the branding of electricity in Icelandic and Lithuanian markets. The literature review provides the main theoretical base for analysis. Furthermore, findings of the research reveal that it is important to create reliability to foster loyalty of business customers to the electricity brand. Some interesting data shows that reputation, trust of the company staff and cooperation are important perceptions for some business customers when choosing an electricity supplier. What is more, while it is difficult to differentiate electricity in and of itself, two distinguishing factors are price and branding service. Finally, research results unveil that some suppliers of electricity in Iceland and Lithuania have created some positive associations about their companies. Lithuania still has its future in creating strong supplier of electricity images in business customers’ minds. Iceland has its own opportunities as well.